(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To compare the mean (days) required for correction of deformity by using classical versus accelerated Ponseti techniques in patients with congenital idiopathic clubfoot. Methods: It was a Randomized controlled trial conducted in General Orthopaedic Ward Ghurki Trust Teaching Hospital affiliated with Lahore Medical & Dental College, Lahore. The Study was carried out over a period of six months from 25-07-2017 to 24-1-2019.The total number of patients were 80 (40 patients in each group) in this study. Group-A was treated with Standard Ponseti (SP) method and group-B was treated with accelerated Ponseti. Results: Patients mean age was 1.6.±0.79 and 1.58±0.79 months in Group A and Group B, respectively. In Group A, 24 patients (60%) and in Group B 18 patients (45%) were males while 16 patients (40%) in Group A and 22 patients (55%) in Group B were females. Comparison of mean time (days) required for correction of deformity were 36.88±5.11 days and 20.73±3.40 in Group A and Group B respectively with p value <0.05. Conclusion: The Accelerated form of Ponseti technique is a very effective way for managing patients with congenital club foot.It reduces the duration of total casting without any effect on outcome as compared to classical method of ponseti.